Қазіргі қазақ әдебиетіндегі түс көру мотиві (А.Алтай «Түсік» әңгімесі негізінде) - Өтебай Ляззат; Серікбай Назерке; Сыздыкова Б.Е. (Research Retrieval and Academic Letters, 2025)
This paper explores the motif of dreaming in contemporary Kazakh literature, with a particular focus on A. Altai’s short story «Tusik (miscarriage)». Dreams in literature serve as a gateway into the complex inner world of characters, revealing their subconscious desires, fears, and moral dilemmas. Drawing on both Freudian and Jungian psychoanalytic theories, the study examines how dreams function as a symbolic representation of the unconscious, providing insight into the psychological and philosophical dimensions of human existence. From a Freudian perspective, dreams reflect repressed wishes and internal conflicts, allowing characters to confront moral and emotional challenges within a symbolic framework. Jungian theory further expands this understanding by interpreting dreams as expressions of archetypes and the collective unconscious, highlighting the mythopoetic and transformative aspects of dream experiences. Through the analysis of «Tusik», the paper demonstrates how the dream motif in Kazakh prose not only advances the narrative but also deepens the psychological portrait of the character, reveals moral and existential crises, and constructs a liminal, metaphysical space between life and death, consciousness and the unconscious. The study concludes that the dream motif in contemporary Kazakh literature is a multi-layered literary device that integrates psychological, philosophical, and mythopoetic functions, enriching both the narrative structure and thematic depth of the work.